2011
DOI: 10.1007/s11626-011-9401-z
|View full text |Cite
|
Sign up to set email alerts
|

In vitro generation of myofibroblasts-like cells from liver epithelial progenitor cells of rhesus monkey (Macaca mulatta)

Abstract: The origin of the myofibroblast, the primary effector cell of liver fibrosis, is still elusive. Here, we report that fluorescence-activated cell sorting purified E-cad + rhesus monkey liver epithelial progenitor cells (mLEPCs) may serve as a potential source for liver myofibroblasts. Adult mLEPCs colonies were cultured in medium containing 2 ng/ml transforming growth factor β (TGF-β) and 10% fetal bovine serum (FBS) to induce differentiation. Phenotypic changes of cells were analyzed by morphological observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…21) β-MNCs are different from SMC progenitor cells or fibroblasts which do not express β-actin and CD 31 . 31) It was reported that resident stem cells/progenitor cells are present in adventitia and can differentiate into SMCs and ECs.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…21) β-MNCs are different from SMC progenitor cells or fibroblasts which do not express β-actin and CD 31 . 31) It was reported that resident stem cells/progenitor cells are present in adventitia and can differentiate into SMCs and ECs.…”
Section: Discussionmentioning
confidence: 95%
“…β-MNCs expressed CD 34 , a marker for bone marrow mesenchymal cells 17) ( Figure 2D to 2D-1), but not CD 31 , a marker for ECs, 17) vimentin, a marker for SMCs and fibroblasts/myofibroblasts, 18,19) α-SMA, a marker for the contractile phenotype of SMCs and fibroblasts/myofibroblasts, 18,19) SM-1, a specific marker for matured SMC, 20) nor N-cadherin, a specific marker for myofibroblasts (Table II). 21) Migration of β-MNCs through the adventitia into the media to become SMCs: At 1-2 weeks, β-MNCs attached to or wrapped around pre-existing small arterioles ( Figures 3B, 3C). In larger arterioles or arteries, β-MNCs with an amoebic configuration migrated through the adventitia into the media ( Figure 3D).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, adjacent slices were immunostained for cell markers using antibodies. The cells in the interstitial space were stained for cell identity of β-SMCs because it was difficult to identify a given cell in the vessel wall using two slices: β-actin (rabbit monoclonal anti-human β-actin antibody, clone AC-15, Sigma Co, St Louis, USA), which is considered to be a cytoplasmic actin and a marker of the synthetic phenotype of vascular smooth muscle cells in vitro; 25) CD 34 (rabbit monoclonal anti-human CD 34 antibody, clone EP 373Y, Epitomics Inc., Burlingame, CA, USA) for bone marrow mesenchymal cells; 26) α-smooth muscle actin (α-SMA; mouse anti-human smooth muscle action, clone/ Klon 1A4, Code No M0851, Dako Epos, Glostrup, Denmark) for contractile phenotype of vascular smooth muscle cells (VSMCs), fibroblasts and myofibroblasts; 27,28) vimentin (rabbit anti-human vimentin antibody, clone Vim 3B4, Code No U7034, Dako Epos) for VSMCs; 27,28) smooth muscle myosin heavy chain -1 (SM-1; mouse monoclonal anti-human smooth muscle myosin heavy chain-1 antibody, clone 3F8, Abcam Co, Cambridge, MA, USA), a specific marker for matured SMCs; 29) N-cadherin, a specific marker for myofibroblasts (rabbit monoclonal anti-human N-cadherin antibody, clone ESR 1792Y, Epitomics Inc); 30) and CD 31 (rabbit monoclonal anti-human CD 31 antibody/PECAM-1, clone EP 3093, Abgent, San Diego, CA, USA) for endothelial cell (ECs).…”
mentioning
confidence: 99%